Tat-NR2B9c Prevents Excitotoxic Neuronal Superoxide Production. Issue 5 (May 2015) - Chen, Yanting; Brennan-Minnella, Angela M; Sheth, Sunil; El-Benna, Jamel; Swanson, Raymond A
The Tat-NR2B9c peptide has shown clinical efficacy as a neuroprotective agent in acute stroke. Tat-NR2B9c is designed to prevent nitric oxide (NO) production by preventing postsynaptic density protein 95 (PSD-95) binding to N -methyl- D -aspartate (NMDA) receptors and neuronal nitric oxide synthase; however, PSD-95 is a scaffolding protein that also couples NMDA receptors to other downstream effects. Here, using neuronal cultures, we show that Tat-NR2B9c also prevents NMDA-induced activation of neuronal NADPH oxidase, thereby blocking superoxide production. Given that both superoxide and NO are required for excitotoxic injury, the neuroprotective effect of Tat-NR2B9c may alternatively be attributable to uncoupling neuronal NADPH oxidase from NMDA receptor activation.